A two-fluid model for refrigerant flow through adiabatic capillary tubes - Seixlack, Andre Luiz [UNESP]; Prata, Alvaro Toubes; Melo, Claudio (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2014)
This work presents a numerical model to simulate refrigerant flow through capillary tubes, commonly used as expansion devices in refrigeration systems. The flow is divided in a single-phase region, where the refrigerant is in the subcooled liquid state, and a region of two-phase flow. The capillary tube is considered straight and horizontal. The flow is taken as one-dimensional and adiabatic. Steady-state condition is also assumed and the metastable flow phenomena are neglected. The two-fluid model, considering the hydrodynamic and thermal non-equilibrium between the liquid and vapor phases, is applied to the two-phase flow region. Comparisons are made with experimental measurements of the mass flow rate and pressure distribution along two capillary tubes working with refrigerant R-134a in different operating conditions. The results indicate that the present model provides a better estimation than the commonly employed homogeneous model. Some computational results referring to the quality, void fraction, velocities, and temperatures of each phase are presented and discussed.
Keywords: Capillary tubes; Two-fluid model; Computer modeling